Level of Adherence and Its Determinants of Prolanis Attendance in Type 2 Diabetes Mellitus Participants at Five BPJS Primary Health Care in Bekasi 2016 - Asfiani, Ledy Visna; Ilyas, Yaslis (UI Scholars Hub, 2017)
The continuity of the participation in Prolanis is one of the primary health care services indicators of commitment, so finding out the level of adherence and the factors influencing it is very important. The aim of the study is to investigate the adherence level of Prolanis participanst and its determinants in type 2 diabetes patients at five BPJS primary health care in Bekasi. This is a cross sectional study, using questionnare to 220 participants with type 2 diabetes by simple random sampling method proportionally. Adherence level of the participants is 3.59 out of 6 times. Length of illness, perceived benefits, perceived barriers and the implementation of the program guidelines are correlated with the adherence level and the dominant factor is perceived barriers. Factors in individual and provider can be used as evaluation tools for the primary health care in facilitating the participants’ needs so that it would increase the level of adherence.